Neighboring ortho‐Hydroxy Group Directed Catalytic Asymmetric Triple Domino Reactions of Acetaldehyde with (E)‐2‐(2‐Nitrovinyl)phenols. Issue 15 (10th April 2014) - Ramachary, Dhevalapally B.; Reddy, P. Srinivasa; Prasad, M. Shiva
Abstract: Herein we demonstrate the utilization of neighboring ortho ‐hydroxy group participation in the pretransition state of enamine‐ and iminium‐based triple domino reactions for high reactions rates and asymmetric induction. Enantiomerically pure, drug‐like chromanes and tetrahydro‐6 H ‐benzo[ c ]chromenes having three to four contiguous stereocenters are synthesized through triple domino Michael/aldol/oxa‐Michael reactions catalyzed by ( R )‐2‐{diphenyl[(trimethylsilyl)oxy]methyl}pyrrolidine followed by Wittig and Michael/Wittig–Horner reactions from simple precursors under mild conditions. Abstract : The utilization of neighboring ortho ‐hydroxy group participation in the pretransition state of enamine/iminium‐based triple domino Michael/aldol/oxa‐Michael reactions catalyzed by ( R )‐DPPOTMS followed by Wittig and Michael/Wittig–Horner reactions is described. Enantiomerically pure chromanes and tetrahydro‐6 H ‐benzo[ c ]chromenes having three to four contiguous stereocenters are synthesized.